Human seroprevalence indicating hantavirus infections in tropical rainforests of Côte d’Ivoire and Democratic Republic of Congo - Witkowski, Peter T.; Leendertz, Siv A. J.; Auste, Brita; Akoua-Koffi, Chantal; Schubert, Grit; Klempa, Boris; Muyembe-Tamfum, Jean-Jacques; Karhemere, Stomy; Leendertz, Fabian H.; Krüger, Detlev H. (Frontiers in Microbiology, 2015)
Hantaviruses are members of the Bunyaviridae family carried by small mammals and causing human hemorrhagic fevers worldwide. In Western Africa, where a variety of hemorrhagic fever viruses occurs, indigenous hantaviruses have been molecularly found in animal reservoirs such as rodents, shrews, and bats since 2006. To investigate the human contact to hantaviruses carried by these hosts and to assess the public health relevance of hantaviruses for humans living in the tropical rainforest regions of Western and Central Africa, we performed a cross-sectional seroprevalence study in the region of Taï National Park in Côte d’Ivoire and the Bandundu region near the Salonga National Park in the Democratic Republic (DR) of Congo. Serum samples were initially screened with enzyme-linked immunosorbent assays using nucleoproteins of several hantaviruses as diagnostic antigens. Positive results were confirmed by Western blotting and immunofluorescence testing. Seroprevalence rates of 3.9% (27/687) and 2.4% (7/295), respectively, were found in the investigated regions in Côte d’Ivoire and the DR Congo. In Côte d’Ivoire, this value was significantly higher than the seroprevalence rates previously reported from the neighboring country Guinea as well as from South Africa. Our study indicates an exposure of humans to hantaviruses in West and Central African tropical rainforest areas. In order to pinpoint the possible existence and frequency of clinical disease caused by hantaviruses in this region of the world, systematic investigations of patients with fever and renal or respiratory symptoms are required.